He, she, it: gender bias in teacher–student interaction at university - Bartulović, Marija pedagoginja; Kušević, Barbara; Širanović, Ana (2012)
Starting from an intercultural education framework, this paper examines whether students at two Zagreb universities perceive interactions with their teachers to be gender influenced. In the first part of the paper, we outline the context of the research and the two theoretical constructs which correspond to traditionally male and female teachers’ performances at university. In the second part of the paper, we present the results of the survey we conducted. The results show that the students recognized some aspects of gender bias in interaction with their teachers and that gendered cultures reflected in the dominantly female or male teachers’ performances were indeed present at the universities included in the survey.
ENG